2010
DOI: 10.1242/jcs.060004
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of an intramitochondrial protein by the cytosolic proteasome

Abstract: Mitochondrial uncoupling protein 2 (UCP2) is implicated in a wide range of pathophysiological processes, including immunity and diabetes mellitus, but its rapid degradation remains uncharacterized. Using pharmacological proteasome inhibitors, immunoprecipitation, dominant negative ubiqbiquitiuitin mutants, cellular fractionation and siRNA techniques, we demonstrate the involvement of the ubiquitin-proteasome system in the rapid degradation of UCP2. Importantly, we resolve the issue of whether intramitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 40 publications
3
76
0
Order By: Relevance
“…The proteasome plays a role in degradation of the intermembrane space protein endonuclease G (30). Uncoupling protein 2 (UCP2), which is an inner mitochondrial membrane protein, can be polyubiquitylated in the mitochondria and then retrotranslocated from the mitochondria to the cytoplasm and degraded by the proteasome (31). In this study, we showed that the mitochondrial protein MTP␣ can be polyubiquitylated and that inactivation of the proteasome prevents its turnover, indicating that MTP␣ is also a target of the UPS.…”
Section: Discussionmentioning
confidence: 85%
“…The proteasome plays a role in degradation of the intermembrane space protein endonuclease G (30). Uncoupling protein 2 (UCP2), which is an inner mitochondrial membrane protein, can be polyubiquitylated in the mitochondria and then retrotranslocated from the mitochondria to the cytoplasm and degraded by the proteasome (31). In this study, we showed that the mitochondrial protein MTP␣ can be polyubiquitylated and that inactivation of the proteasome prevents its turnover, indicating that MTP␣ is also a target of the UPS.…”
Section: Discussionmentioning
confidence: 85%
“…Treatment of the fibroblast cultures with MG132, an inhibitor of proteasome, as well as of mitochondrial Lon protease [35,36], prevented the KH7-induced decrease of the level of NDUFA9, NDUFS4 and NDUFV2 in the fibroblast lysate (Fig. 5A).…”
Section: Effect In Fibroblast Cultures Of Protease Inhibitors On the mentioning
confidence: 91%
“…The level of the mature, nuclear-encoded subunits of complex I is likely to be determined by the balance between their expression, mitochondrial import/maturation, and proteolytic digestion by mitochondrial proteases, as well as by the proteasome, for those copies of the subunits which undergo retrograde back diffusion in the cytosol (see [21,35]). Treatment of the fibroblast cultures with MG132, an inhibitor of proteasome, as well as of mitochondrial Lon protease [35,36], prevented the KH7-induced decrease of the level of NDUFA9, NDUFS4 and NDUFV2 in the fibroblast lysate (Fig.…”
Section: Effect In Fibroblast Cultures Of Protease Inhibitors On the mentioning
confidence: 99%
“…Experiments with isolated energized mitochondria have suggested that non-mitochondrial factors are needed for rapid proteolytic degradation of these UCPs. Indeed, the cytosolic proteosome promotes rapid degradation of UCP2 and UCP3, while UCP1 and ANT are not degraded by this machinery [302,303]. In fact, this has been the first demonstration that the IMM proteins are degraded by the cytosolic ubiquitin-proteosome system.…”
Section: Ucp Activity and Its Regulationmentioning
confidence: 92%